Investigation of impact of a crumb rubbergranulate addition on the asphalt mixtures resistanceto water and frost - Wiśniewski, Damian; Selke, Milena; Smolińska, Anna; Słowik, Mieczysław (Budownictwo i Architektura / Civil and Architectural Engineering, 2019)
The article presents the results of the tests of hot mix asphalt (HMA) modi-fi ed with the addition of crumb rubber granulate using the dry method. This modifi cation consisted in the applying of rubber granules into the aggregate mixture, replacing a 0/2 mm fraction of the basalt aggregate. The tests were carried out for the Asphalt Concrete to be used in binder course of a road pavement (AC16W 50/70). There were 5 types of HMA analyzed: without the addition of rubber granules as well as with 1% or 2% (in relation to the weight of the aggregate mix) of activated with a grain size up to 2 mm and non-activated rubber granules with the same grain size. The activation process was carried out using an electro-magnetic mill with a microwave generator, centrifugal rotor mill with supersonic speed and auxiliary equipment. For each analyzed mixture type, density, bulk density, air voids and resistance to water and frost were determined. On the basis of the research, it was observed that the addition of crumb rubber granules to HMA adversely affects the air voids content causing its increase. The addition of crumb rubber granulate also affects the resistance of HMA to water and frost, but the quantitative changes depend on the amount of added crumb rubber granulate.